Assessment of interocular symmetry of choroidal vascularity index and thickness in patients with systemic sclerosis: a prospective study - Raciborska, Anna; Pieklarz, Barbara; Gińdzieńska-Sieśkiewicz, Ewa; Zonenberg, Agnieszka; Kowal-Bielecka, Otylia; Konopińska, Joanna; Dmuchowska, Diana A. (Frontiers in Medicine, 2025)
PurposeSystemic sclerosis (SSc) affects blood vessels, internal organs, and skin. In ophthalmology, SSc impacts the choroid. The choroidal vascularity index (CVI) measures the vascular component of the choroid and may serve as a biomarker for the disease staging and prognosis. Studies have reported reduced choroidal thickness and altered CVI in SSc, which supports the theory of vascular damage. This study aimed to examine interocular symmetry in choroidal parameters among SSc patients. It has provided the insight into the disease symmetry and assessed the representativeness of examining one eye.MethodsThis prospective single-center cross-sectional study included 33 patients with SSc and 40 healthy controls. The patients underwent ophthalmological examination (including refraction, visual acuity, IOP, biometry, slit-lamp biomicroscopy, dilated fundus examination, and spectral-domain optical coherence tomography) and rheumatological evaluation. Various parameters of the choroid in the macular and peripapillary regions were analyzed, including choroidal thickness, choroidal volume, and CVI. The interocular asymmetry in the choroidal parameters was quantified using signed and absolute differences. The correlation analysis between the left and right eyes was based on the intraclass correlation coefficient (ICC), Spearman’s correlation coefficient, and paired Wilcoxon test.ResultsThere were no significant differences in the macular and peripapillary choroidal parameters between fellow eyes in both SSc patients and controls (p > 0.05). The parameter that showed the lowest correlation among those examined was CVI—in both groups, as well as in both examined areas. The interocular correlation of choroidal parameters was stronger in the peripapillary area than in the macular area in both groups. In general, the results were confirmed in subgroup analyses stratified according to sex, SSc subtype, Scl70 antibody positivity and previous and/or active digital ulcers.ConclusionThere is interocular symmetry of the choroidal parameters in patients with SSc and controls included in our study. The parameters from one eye are representative of the fellow eye of a given patient. This conclusion may contribute to the design and interpretation of future studies. It also broadens our knowledge of SSc pathophysiology.